Analysis of Word Formation in Slang Words Found in The Movie "Big Daddy" - Hafiz Kurnia Yahya; Havid Ardi (English Language and Literature, 2023)
ABSTRACTKurnia Yahya, Hafiz. 2023. “Analysis of Word Formation in Slang Words Find The Movie Big Daddy ”. Thesis. Fakultas Bahasa dan Seni. Universitas Negeri Padang.This research aims to find slang words and word formation processes used in a film script. Then, this research uses descriptive method. The data used is the Big Daddy film script using the Yule Theory. Researchers found 256 slang words and there were 71 data that had been found and identified. Then, the researchers found that there were five types of slang formation used from the Big Daddy film, namely coinage, blending, clipping, compounding, and borrowing. The researcher found that the dominant type of slang word used was Coinage.